Urinary catheterization management after vaginal prolapse surgery: A national survey among Chinese urogynecologists and nurses - Yiqian Chen; Yi Liang; Xiaodan Li; Xiuli Sun; Jianliu Wang (BMJ Publishing Group, 2022)
Background: Urinary catheterization after vaginal prolapse surgery can cause inconvenience for patients, elevate the risk of urinary tract infections, and potentially prolong the hospitalization. In China, there is no consensus on the optimal time to remove the urinary catheter after vaginal prolapse surgery. Thus, it will be valuable to gain insight into the nationwide catheterization management after the vaginal prolapse surgery. Methods: From March to May 2020, an online questionnaire was shared and purposive non-probabilistic sampling was used to recruit the participants. The urogynecologists currently performing vaginal prolapse surgery and involved nurses were included in this study. Results: 1363 urogynecologists and 436 nurses responded and 99.5% of them reported using transurethral indwelling catheters (TIC) for post-operative bladder drainage in their practices. The duration of initial catheterization after vaginal prolapse surgery was generally 1-7 days, with a median duration of 3 days for anterior colporrhaphy (AC) and anterior & posterior colporrhaphy (APC), and 2 days for other procedures. For the same type of surgery, the median duration of catheterization varied by region. For AC, it was shorter by 1 day in West China and South China (P ​< ​0.001); for PC, it was 2 days in most regions, while 1 day in East China (P ​< ​0.05); and for APC, it was 3 days in most regions, while 4 days in Northeast China (P ​< ​0.05). No statistically significant difference was found in duration of catheterization in hospital levels. Conclusions: The findings suggested that duration of catheterization after prolapse surgery varied greatly in China, potentially resulting in unnecessary prolonging of catheterization. Well-designed studies are urgently needed to optimize catheterization management after vaginal prolapse surgery in China.